Innovative Practices Of Socially Oriented Non-Profit Organizations On Family And Children's Affairs In Russia - Grozdilov, S.; Katayeva, V.; Fomichyova, T. (Living Standards of the Population in the Regions of Russia, 2018)
The activities of non-governmental non-profit organizations in the Russian Federation. The work of socially-oriented non-governmental non-profit organizations with families and children is considered in more detail. The statistical data of the Ministry of Justice for the Federal Districts of the Russian Federation are taken as a basis. The Object of the Study. Socially-oriented non-governmental non-profit organizations with families and children registered in the territory of the Russian Federation. The Subject of the Study. Innovative practices of socially-oriented non-profit organizations for family and children in Russia. The Purpose of the Study is reviewing innovative practices of socially-oriented non-profit organizations for family and children in Russia. The Theoretical Aspect of the subject is studing conceptual approaches to the study of the activities of socially-oriented non-state non-profit organizations with families and children in theoretical sociology. The Empirical Aspect of the Subject is studing innovative practices of socially-oriented non-profit organizations for family and children in Russia for empirical measurements.The Main Theoretical Provisions of the Article are practices of socially-oriented non-profit organizations as a functional aspect of studying the activities of these organizations in Russia. The role of the non-profit sector in the development of the country's economy is revealed. Programs of state support for socially-oriented non-profit organizations are analyzed. The subjects of the Russian Federation are singled out - the leaders in terms of the number of non-profit organizations and the number of NGOs working with families and children. The article describes and classifies the areas of activity of non-profit organizations for working with families and children, and innovative models of this kind of activity are identified. As a result of the analysis, a number of systemic problems are highlighted that can hamper the development of socially-oriented non-profit organizations aimed at supporting families and children. When working on this research specific methods of document analysis were used: traditional (primary) document analysis as well as secondary, comparative analysis. Thus, a "triangular approach" is applied to research innovative practices of socially oriented non-profit organizations.